2015
DOI: 10.1159/000374055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Donor Age, Long-Term Passage Culture, and Cryopreservation on Tonsil-Derived Mesenchymal Stem Cells

Abstract: Objectives: Human mesenchymal stem cells (MSCs) are efficacious in various cellular therapeutic applications and have been isolated from several tissues. Recent studies have reported that human tonsil tissue contains a new source of progenitor cells, potentially applicable for cell-based therapies. Information about the effects of donor age, long-term passage and cryopreservation are essential for clinical applications and cell-based therapies. Therefore, the authors investigated how the morphology, cell-surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…As tonsillar tissues are discarded after surgery, the isolation of stem cells from these discarded tissues offers another valuable means of recycling human tissue for stem cell therapy [20,23]. In addition, the T-MSCs have MSC characteristics and are known to secrete various cytokines [27], growth factors [28], and exosomes [29] considered suitable for cell therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As tonsillar tissues are discarded after surgery, the isolation of stem cells from these discarded tissues offers another valuable means of recycling human tissue for stem cell therapy [20,23]. In addition, the T-MSCs have MSC characteristics and are known to secrete various cytokines [27], growth factors [28], and exosomes [29] considered suitable for cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the T-MSCs have MSC characteristics and are known to secrete various cytokines [27], growth factors [28], and exosomes [29] considered suitable for cell therapy. The T-MSCs show excellent immune modulation activity and no immunologic problems even when the T-MSCs were combined from three independent donors [23]. Thus, we speculated that the T-MSCs would be suitable for clinical use as a heterologous transplantation cell source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was widely believed that mesenchymal stem cells (MSCs) were multipotential fibroblast-like cells with CD73+, CD105+, CD14-, CD34-and CD45-and plastic adherent [25][26][27]. Recent studies had revealed that fibroblasts shared much more in common than previously recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported the isolation of tonsilMSCs (T-MSCs) from tonsil tissues and found that the morphology, cell-surface markers, proliferation potential, and differentiation potential of T-MSCs were similar to those of BMMSCs [11,15]. T-MSCs were considered to be promising MSCs that could be used as future alternative sources for autologous or allogenic MSCs, because the effects of donor age, longterm passage culture, and cryopreservation on T-MSC properties were negligible [11,15]. Despite the reports of T-MSCs as a new autologous or homologous source of MSCs, there have been no reports on specific markers of MSCs for purified T-MSC isolation.…”
Section: Introductionmentioning
confidence: 99%